Chronic joint pain 3 years after Chikungunya virus infection largely characterized by relapsing-remitting symptoms (2020)
OBJECTIVE: To determine the frequency of chronic joint pain and stiffness 3 years after infection with chikungunya virus (CHIKV) in a Latin American cohort. METHODS: A cross-sectional followup of 120 patients from an initial cohort of 500 patients who reported joint pain 2 years after infection from the Atlántico Department, Colombia. Patients were clinically diagnosed as having CHIKV during the 2014-2015 epidemic, and baseline and followup symptoms at 40 months were evaluated in serologically confirmed cases. RESULTS: Of the initial 500 patients enrolled in the study, 482 had serologically confirmed chikungunya infection. From this group, 123 patients reported joint pain 20 months after infection, and 54% of those patients reported continued joint pain 40 months after infection. Therefore, 1 out of every 8 people who tested serologically positive for CHIKV infection had persistent joint pain 3 years after infection. Participants who followed up in person were predominantly adult (mean ± SD age 51 ± 14 yrs) and female (86%). The most common type of pain reported in these patients at 40 months post-infection was pain with periods of relief and subsequent reoccurrence, and over 75% reported stiffness after immobility, with 39% experiencing morning stiffness. CONCLUSION: To our knowledge, this is the first report to describe persistent joint pain and stiffness 40 months after viral infection. The high frequency of chronic disease highlights the need to develop prevention and treatment methods. Further studies should be conducted to understand the similarities between post-chikungunya joint pain and rheumatoid